The importance of literature reviews in small business and entrepreneurship research. (4th May 2023) - Kraus, Sascha; Mahto, Raj V.; Walsh, Steven T.
ABSTRACT: Literature in a discipline generally represents the advancement of knowledge and a richer understanding of associated phenomena, factors, and context. However, an unplanned growth in literature can impede advancement by introducing the possibility of complex, competing, and occasionally counterintuitive arguments in the ongoing scholarly dialogue. The exponential growth of literature in small business and entrepreneurship research in recent years has made salient just such risk. Thus, there is an urgent need for developing a clear understanding of advancements and state of knowledge stock in the discipline to inform and guide future researchers aiming to advance the field. The Journal of Small Business Management's first special issue on review articles intends to contribute to the advancement of small business and entrepreneurship literature by informing researchers on the current state of research.